WTO DALAM PENYELESAIAN SENGKETA PERDAGANGAN IMPOR BAJA GALVALUME ANTARA INDONESIA DAN VIETNAM - Ade Maryanto; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research will describe the role of the World Trade Organization on settlement the trade dispute between Indonesia and Vietnam. The method of analysis used in this study is a qualitative research. This study used the perspective of Neoliberalism which consider that the state is not the only one actors who played a role in international relations. Neoliberalism is the theory that descibes concepts of rationality and contract, and focuses on the role of institutions and organizations in international politics.One of the functions of the WTO is to be an formal forum trade disputes for it’s member countries. One such trade disputes has been involving among Indonesia and Vietnam on 2014, right after Indonesia imposed a specific duty on galvalume steel product. This duty means to be a safeguard measures meaning of the WTO Agreement on Safeguards. Vietnam’s as one of the main importing country of galvalume to Indonesia complaint this duty to WTO. Vietnam’s argued that if the duty were disriminated because exclude Vietnam from 120 other developing countries which have been extempted from the Spesefic Duty regulated on PMK No. 137/PMK.011/2014, and in the duty any event inconsistent with Indonesia’s MFN obligation under GATT Article I. In the settlement of this trade disputes, WTO consider the Spesific Duty has imposed by Indonesia is not a safeguard measures as regulated on the Agreement on Safeguard. On 12 March 2019 Indonesia has Stopped the Spesific Duty regulated through the PMK No.26/PMK.010/2019. Kata kunci: WTO, Disputte Settlement, Neoliberalism, Safeguard, Political Economy